Multidimensional quantum mechanical modeling of electron transfer and electronic coherence in plant cryptochromes: the role of initial bath conditions - Mendive-Tapia, David; Meyer, Hans-Dieter (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2018)
A multidimensional quantum mechanical protocol is used to describe the photoinduced electron transfer and electronic coherence in plant cryptochromes without any semiempirical, e.g., experimentally obtained, parameters. Starting from a two-level spin-boson Hamiltonian we look at the effect that the initial photoinduced nuclear bath distribution has on an intermediate step of this biological electron transfer cascade for two idealized cases. The first assumes a slow equilibration of the nuclear bath with respect to the previous electron transfer step that leads to an ultrafast decay with little temperature dependence; while the second assumes a prior fast bath equilibration on the donor potential energy surface leading to a much slower decay, which contrarily displays a high temperature dependence and a better agreement with previous theoretical and experimental results. Beyond Marcus and semiclassical pictures these results unravel the strong impact that the presence or not of equilibrium initial conditions has on the electronic population and coherence dynamics at the quantum dynamics level in this and conceivably in other biological electron transfer cascades.